MODEL PENGATURAN PENGAMPUAN PARSIAL UNTUK LANJUT USIA SEBAGAI JAMINAN PERLINDUNGAN HUKUM DI INDONESIA - Raharningtyas Marditia, Putri Purbasari (Jurnal Paradigma Hukum Pembangunan, 2023)
The background for writing this article was based on the publication on September 14, 2021, of Presidential Regulation Number 88 of 2021 concerning Old Age. The presidential regulation explains that to realize independent, prosperous, and dignified elderly people, cross-sectoral coordination is needed between the Central Government, Regional Governments, and all stakeholders. Based on this situation, the author through this paper offers the idea of legal protection that can support the capacity building of the elderly by continuing to pay attention to the guarantee of its implementation as a legal subject that has Subjective Rights and Objective Rights. So based on this, the author offers the concept of a Partial Supporting Regulatory Model for Seniors as a Guarantee of Legal Protection. The method used is normative legal research. This research was conducted using a library-based approach that focuses on reading and examining primary and secondary legal sources, through the statutory approach. The result of this paper is a Recommendation Model for Setting Partial Support for the Elderly as a Guarantee of Legal Protection, this partial coverage for the elderly aims to provide this system will provide legal protection that is far more measurable because a person who is given amnesty is still given the freedom to decide for himself what is to be his will with the help of the beneficiary. These recommendations will be included in the regulatory model.